Enhanced humanization and affinity maturation of neutralizing anti‐hepatitis B virus preS1 antibody based on antigen–antibody complex structure. Issue 2 (4th December 2014) - Kim, Jin Hong; Gripon, Philippe; Bouezzedine, Fidaa; Jeong, Mun Sik; Chi, Seung-Wook; Ryu, Seong-Eon; Hong, Hyo Jeong
Abstract : To improve a previously constructed broadly neutralizing hepatitis B virus (HBV)‐specific preS1 humanized antibody (HzKR127), we further humanized it through specificity‐determining residue (SDR) grafting. Moreover, we improved affinity by mutating two residues in heavy‐chain complementarity‐determining regions (CDR), on the basis of the crystal structure of the antigen–antibody complex. HzKR127‐3.2 exhibited 2.5‐fold higher affinity and enhanced virus‐neutralizing activity compared to the original KR127 antibody and showed less immunogenic potential than HzKR127. Enhanced virus‐neutralizing activity was achieved by the increased association rate, providing insights into engineering potent antibody therapeutics for HBV immunoprophylaxis. HzKR127‐3.2 may be a good candidate for HBV immunoprophylaxis. Abstract : Anti‐hepatitis B virus preS1 humanized antibody was constructed by SDR grafting. SDR‐grafted humanized antibody was affinity‐matured by mutating two HCDR residues. Affinity matured humanized antibody exhibits enhanced HBV‐neutralizing activity. Enhanced HBV‐neutralizing activity was achieved by an increased association rate.